Characterization of Acoustic Emission Parameters during Fracture Process of Siltstone with Prefabricated Void. (27th July 2022) - Liu, Xiaorong; Zheng, Lulin; He, Hengyi; Qiu, Qing; Liu, Ziqi; Li, Xuefeng; Yan, Lin; Huang, Gang
Abstract : Due to the transfer of Lannigou gold mining from shallow to deep, a series of stability problems of surrounding rock have been caused. The drilling pressure relief technology has unique advantages in the control of mine pressure in high-stress roadways. In order to explore the damage effect of borehole pressure relief technology on rock, uniaxial compression and acoustic emission tests were carried out on siltstone specimens with borehole diameters of 8 mm, 12 mm, and 16 mm, respectively, and the acoustic emission signals of the whole process were collected simultaneously to explore the uniaxial compression of siltstone specimens with prefabricated holes in this paper. According to the statistical characteristics of acoustic emission, the damage law of siltstone specimens with prefabricated holes was explored from the microscopic point of view and the damage effect of drilling on siltstone specimens reflected by the acoustic emission phenomenon was revealed. The research results show that there are multiple stress drops before the deformation and failure of the rock sample with prefabricated drill holes; there is a positive correlation between the diameter of the drill hole and the power law index of the stress drop distribution; the acoustic emission activity of the rock during the deformation and failure process can be indirectly reflected the evolution of microfractures; the energy probability density function under different borehole diameters conforms to the power law distribution; the critical exponent obtained by the maximum likelihood estimation has an optimal plateau value, which can accurately characterize the power exponent of the energy distribution; the launch waiting time and aftershock sequence have a good power-law distribution in logarithmic coordinates. The research results provide a certain theoretical basis for the application of drilling pressure relief technology in southwestern Guizhou.